Visual culture approaches to the selfie - Murray, Derek Conrad (Routledge history of photography, 2022)
"This collection explores the cultural fascination with social media forms of self-portraiture, "selfies," with a specific interest in online self-imaging strategies in a Western context. The book examines the selfie as a social and technological phenomenon, but also engages with digital self-portraiture as representation: as work that is committed to rigorous object-based analysis. The scholars in this volume consider the topic of online self-portraiture - both its social function as a technology-driven form of visual communication, as well as its thematic, intellectual, historical, and aesthetic intersections with the history of art and visual culture. This book will be of interest to scholars of photography, art history, and media studies"- Resumé vydavatel